Psychological Features of Initiative in Groups with High and Low Creativity Level - N F Shlyakhta; A S Zharikova (Peoples' Friendship University of Russia (RUDN University), 2011)
In this research the comparative analysis of the significance of different parameters of initiative in groups with different level of creativity is submitted. As a result of which some specific qualities of the initiative in each group were revealed. Practical recommendations on the development of initiative were given.